ナンキョク ミズホ コウゲン ニ オケル チジキ サン セイブン ノ ブンプ - 吉村, 愛一郎; ヨシムラ, アイイチロウ; 阿部, 義昭; アベ, ヨシアキ; 成瀬, 廉二; ナルセ, レンジ; Yoshimura, Aiichiro; Abe, Yoshiaki; Naruse, Renji (国立極地研究所, 1977)
P(論文) 南極みずほ高原の氷床上において,1968年から1974年(第8,9,10,11,14次南極地域観測隊)にかけて行われた地磁気測量の結果をまとめ,同地域の地磁気偏角,伏角,全磁力の分布図を得た.年度化成を行った年は1970.0年である.地磁気局地異常の一つはサンダーコックヌナタクスの南西地域に,一つは昭和基地とみずほ観測拠点の中間地域に見られた.両地域と払重力異常の大きい地域に一致する. Distributional maps of declination, inclination and total force of geomagnetism reduced to the epoch of 1970.0 are presented on the basis of the data obtained by the oversnow traverses during the period from 1968 to 1974 over Mizuho Plateau, East Antarctica. One of the local magnetic anomalies appears in a region to the southwest of Sandercock Nunataks and another between Syowa Station and Mizuho Camp. They coincide well with the regions where the large gravity anomalies are given. departmental bulletin paper